2017 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--28925
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Sustainable Engineering and Industrial Ecology using a Hybrid Problem-Project Based Learning Approach

Abstract: Dr. Torres, a native of New Mexico, joined the Department of Engineering Technology (Concrete Industry Management program) in August 2013 where he teaches Concrete Construction Methods and a variety of project management courses. He received both of his graduate degrees, Ph.D. and M.S., in Civil Engineering (Structural), from the University of New Mexico. He obtained his B.S. degree, also in Civil Engineering, from New Mexico State University. Dr. Torres' research areas include the science and advancement of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 7 publications
(8 reference statements)
1
12
0
Order By: Relevance
“…This mirrors the outcome of the literature review in Section 3.1 , where several authors (e.g. Margallo et al 2019 ; Sriraman et al 2017a , b ) emphasize the importance of project- and problem-based learning approaches and others provide examples of real-life company cases being the core element of their teaching concepts (see Cosme et al 2019 ; Lockrey and Bissett Johnson 2013 ; Piekarski et al 2019 ).…”
Section: Resultssupporting
confidence: 56%
See 2 more Smart Citations
“…This mirrors the outcome of the literature review in Section 3.1 , where several authors (e.g. Margallo et al 2019 ; Sriraman et al 2017a , b ) emphasize the importance of project- and problem-based learning approaches and others provide examples of real-life company cases being the core element of their teaching concepts (see Cosme et al 2019 ; Lockrey and Bissett Johnson 2013 ; Piekarski et al 2019 ).…”
Section: Resultssupporting
confidence: 56%
“…Different authors reported the relevance of project-based learning (e.g. Lockrey and Bissett Johnson 2013 ; Margallo et al 2019 ; Piekarski et al 2019 ; Sriraman et al 2017a , b ), most of the time through a life cycle assessment project developed by the students and using one or different LCA commercial software. Some studies presented experiences with cases developed in partnership with industrial partners (Cosme et al 2019 ; Piekarski et al 2019 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many professional organizations are establishing Sustainability forums and consortiums, as well as renowned universities have included courses in sustainable engineering, industrial ecology and ecodesign in their engineering/technology curriculum to better prepare tomorrow's chemical engineering professional (Sriraman et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Environmental education has been marked by numerous facts, which are bases for developments seen today (Leal Filho et al, 2015), for example, the Industrial Ecology (IE) and some of its central concepts, such as Ecodesign and LCA, have been gaining worldwide importance (Boyle, 2004;Cushman-Roisin et al, 1999;Sriraman et al, 2017). Sustainability has been a key driver in the education of engineers (Lockrey and Johnson, 2013) for when they leave university they will be responsible for putting into practice all their learning towards cleaner and more sustainable practices in the conception, redesign, engineering and reengineering and management of products, processes and services.…”
Section: Teaching Life Cycle Assessment and Ecodesign In Engineering Coursesmentioning
confidence: 99%